(untitled) (Research, Society and Development, 2022)
Visceral leishmaniasis (VL) was considered non-endemic in the southern region of the country until 2006 when there was the first notification of na autochthonous canine case in the municipality of São Borja in Rio Grande do Sul. The states of Santa Catarina and Paraná the autochthony in canines occurred in the years 2010 and 2012 respectively. In the southern region, dueto its recent installation in addition to the few notifications, there is a lack of inclusion of the disease in differential diagnoses in human and veterinary clinics being the prevalence of VL is greater than the record on notified cases.Thus, the objective was to review the situation of human and canine VL and the presence of vectors in the southern region of the country. Official publications on the disease between 2009 and 2020 were considered and online journal data bases were consulted. Conflicting in formation was found regarding the number of cases and location of the infection, which maybe a consequence of the change in the standardization of human VL records, decentralization and lack of uniformity in CVL records, in addition to the dissemination of diagnoses through out dated annual epidemiological bulletins The sandfly Lutzomyia gaminarai, an endemic species in southern Brazil, requires attention from surveillance and researchers dueto its phylogenetic proximity to Lutzomyia longipalpis.